The Role of Women in Islamic Education the Process of Transformation to Modernity - Ramadhina Nida'an Khofiyya; Naila Tazkiyatan; Darnoto Darnoto (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2024)
particularly in the last few decades. Nevertheless, women are occasionally the victims of social injustice and are consequently regarded as inferior beings. The Islamic tradition, as set forth in the Quran and the hadith, espouses the view that there is no distinction between the rights of men and women. Both genders are provided with an equal opportunity for personal and professional growth across a range of societal roles. This research employs qualitative methods and a literature review. The objective of this research project is to examine the role of women and their rights in the context of Islamic teachings. The study will address two key objectives. The primary objective of this study is to elucidate the role and rights of women in an Islamic perspective. The objective is to identify and analyze the challenges and obstacles that women continue to face in accessing equal educational and economic opportunities, as well as other sectors. These obstacles are shaped by a complex interplay of social norms, conservative religious interpretations, and socio-cultural and structural challenges. To achieve complete gender equality, it is imperative to address these impediments and dismantle the structural barriers that impede women's advancement.